CLINICAL OUTCOMES OF LAYERED LITHIUM DISILICATE RESTORATIONS: A RETROSPECTIVE ANALYSIS - Dan Lolos; Roxana Buzatu; Roxana Oancea; Stefania Dinu; Anca Tudor; Sorin Gheorghe Mihali (Romanian Journal of Oral Rehabilitation)
This study investigates the survival rates and failure modes of layered lithium disilicate restorations with feldspathic ceramic layering, observing a total of 546 restorations across 62 patients, evenly distributed by gender (31 males and 31 females), over an average follow-up period of 52.1 months. The findings reveal an impressive overall survival rate of 97.6%, with 13 failures identified, predominantly fractures (8 cases), followed by debonding (2 cases) and dyschromia (2 cases). Kaplan-Meier analysis demonstrated no statistically significant differences in survival rates between male and female patients (Log Rank Test, p=0.877), although males exhibited a marginally longer mean survival time. These results correspond with existing literature that emphasizes the prevalence of fractures in layered restorations, particularly in high-stress areas. The study suggests that careful consideration of clinical factors is essential for optimizing the performance of these restorations. Future research should focus on exploring various restoration designs and conducting prospective studies in standardized settings to validate these findings and improve clinical protocols.